Effect of Sappan Wood Ethanol Extract in CRP Level and Phagocytic Index Between Group of Mice Infected with S. aureus and E. coli - Rohmah, Martina Kurnia; Hisbiyah, A'yunil; Octivani, Amellya; Anwari, Farida (Universitas Pakuan, 2024)
S.aureusand E.coli are pathogenic bacterial that cause many infectious disease in the world. Immunomodulator is needed to prepare the immune system to be able against the infection. Some parameters usually used to assess the immunomodulatory activity such as C-Reactive Protein (CRP) and phagocytic index. This study aims to investigate the difference effect of sappan1wood extract in CRP level and phagocytic index between group mice infected with S. aureus and E. coli. Two treatment groups of mice were prepared for S. aureus and E. coli test. Each group subjected to 7 treatments i.e. (1) Normal mice1(CMC-Na 1 %- Merck® 217277), 1(2) Negative Control (bacterial infection + CMC-Na 1 %),11(3) Positive Control (bacterial infection + Imboost force®1treatment, PT SOHO Industri Pharmasi), (4) Bacterial infection and EESW treatment 25 mg/kg BW, (5) 50 mg/kg BW, (6) 100 mg/kg BW, and (7) 200 mg/kg BW. Mice blood was taken to detect the CRP and phagocytic index after treatment. The T test showed that there was a significant difference between CRP levels (p0.05) and phagocytic index (p0.05) of S. aureus and E. coli group. EESW 200 mg/kg BW reduced CRP level to 11 mg/dL (S. aureus) and 6 mg/dL in (E. coli). EESW 200 mg/kg BW increased phagocytosis to 1.54 folds (S. aureus) and 4.62 folds (E. coli). Sappan wood ethanol extract effect to CRP level and phagocytic index1in mice group infected with E. coli is better than S. aureus1infection group.